Development of a universal real-time RT-PCR assay for detection of pan-SARS-coronaviruses with an RNA-based internal control - Yu, Beibei; Xu, Changping; Huang, Shiwang; Ni, Jun; Zhou, Jiancang; Zhang, Yuting; Wu, Maomao; Zhang, Jun; Fang, Lei (Frontiers in Microbiology, 2023)
The current pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exemplifies the critical need for rapid diagnostic assays to prompt intensified virological monitoring both in human and wild animal populations. To date, there were no clinical validated assays for pan-SARS-coronavirus (pan-SARS-CoV) detection. Here we suggest an innovative primer design strategy for the qualitative reverse transcription-PCR (RT-qPCR) diagnosis of pan-SARS-CoVs targeting the envelope (E) gene. Furthermore, we developed a new primer-probe set targeting human β2-microglobulin (B2M) as an RNA based internal control for process efficacy. The universal RT-qPCR assay demonstrated no false-positive amplifications with other human coronaviruses or 20 common respiratory viruses and its limit of detection (LOD) was 159.16 copies/mL at 95% detection probability. In clinical validation, the assay delivered 100% sensitive results in the detection of SARS-CoV-2-positive oropharyngeal samples (n=120), including three variants of concern (Wuhan, Delta and Omicron). Taken together, this universal RT-qPCR assay provides a highly sensitive, robust, and rapid detection of SARS-CoV-1, SARS-CoV-2, and animal-derived SARS-related CoVs.